PRODUÇÃO DE MATERIAIS DIDÁTICOS VIRTUAIS INTERATIVOS PARA OS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Pereira, Tânia M.; Costa, Juliane S. P.; Brizzi, Maristela L. S. (Salão do Conhecimento, 2013)
Resumo